Audiobook Industry: Reading by Using Ear in the Digital Age - Elislah, Neli; Irwansyah, Irwansyah (UI Scholars Hub, 2022)
As a medium for reading books through audio formats, digital audiobook are experiencing significant growth in popularity with a more diverse audience than ever before during the COVID-19 pandemic. Book publishers have begun to evolve to consider publishing books in audio format, in addition, the presence of audiobook on various alternative platforms based on streaming and subscription offers convenience to read a book. This study aims to survey the development of audiobook in the current digital era, especially in Indonesia with the presence of streaming and subscription media platforms. Furthermore, by reassessing the concept of reading books in the digital era to understand reading an audiobook through hearing. By using the literature review method, this research has seen a change in the conception of reading books which was previously only associated with reading writing through the eyes, because the presence of digital audiobook allows readers to carry out reading activities with high mobility by only through the eyes or the sense of hearing. Simplicity through listening activities brings audiobook into popular media that is present in various learning activities in Indonesia and also brings new experiences in enjoying literature through sound that offers readers to read books by listening. Reading is an important part of learning, with every day audiobook are increasing literacy through new reading media. Flexibility for readers aside from making audiobook a product of written books by offering readers the option to choose a format that supports their literacy and literary experience. This research provides findings for the audio industry, which is currently popular as well as an alternative in the reading industry, especially in Indonesia in today’s digital era.